Development of reading comprehension with graphic organizers for students with dyslexia - Jacqueline Lopez; Johnny Campoverde (OmniaScience, 2018)
The executed research will permit the creation and design of a handbook with easy-to-read stories that would increase their receptive abilities in a foreign language in the learning process of students with learning disabilities (dyslexia). This academic work has also the aim of analyzing the impact of graphic organizers in the development of reading comprehension accordance  with the level of English of each student. The theoretical foundation is constructed by the contents previously defined in the problem; with specific bibliography for the scientific content. Statistical analyses of information were taken into consideration. These analyses determined the importance of the implementation of a handbook that would include a short and a long text, vocabulary in context, strategies to improve reading skills, and unit assessments to evaluate the knowledge of students in each unit. This will let the students to develop multiple skills with the guidance of the teacher. This innovative material has as a main target to help the learner to decode phonemes and to identify structures of the story through charts and pictures.